Diversity and Distribution of Freshwater Aerobic Anoxygenic Phototrophic Bacteria across a Wide Latitudinal Gradient - Ferrera, Isabel; Sarmento, Hugo; Priscu, John C.; Chiuchiolo, Amy; González, José M.; Grossart, Hans-Peter (Frontiers in Microbiology, 2017)
Aerobic anoxygenic phototrophs (AAPs) have been shown to exist in numerous marine and brackish environments where they are hypothesized to play important ecological roles. Despite their potential significance, the study of freshwater AAPs is in its infancy and limited to local investigations. Here, we explore the occurrence, diversity and distribution of AAPs in lakes covering a wide latitudinal gradient: Mongolian and German lakes located in temperate regions of Eurasia, tropical Great East African lakes and polar permanently ice-covered Antarctic lakes. Our results show a widespread distribution of AAPs in lakes with contrasting environmental conditions and confirm that this group is composed of different members of the Alpha- and Betaproteobacteria. While latitude does not seem to strongly influence AAP abundance, clear patterns of community structure and composition along geographic regions were observed as indicated by a strong macro-geographical signal in the taxonomical composition of AAPs. Overall, our results suggest that the distribution patterns of freshwater AAPs are likely driven by a combination of small-scale environmental conditions (specific of each lake and region) and large-scale geographic factors (climatic regions across a latitudinal gradient).